KEFEKTIFAN MODEL DIRECT LEARNING TERHADAP KEMAMPUAN MENULIS CERPEN MTS MAMBAUL HISAN - Hamidah; Wardiah, Dessy; Murniviyanti, Liza (Universitas PGRI Palembang, 2022)
This study is entitled The Effectiveness of Direct Learning Model on the Ability to Write Short Stories for Class VIII Students MTS Mambaul Hisan Sungai Lilin (Candle River). The formulation of this research problem is